A report from VIS 2016 - Comba, Joao; Sadlo, Filip; Weiskopf, Daniel (Computing in science and engineering, 2017)
IEEE VIS 2016 brought together researchers and practitioners to discuss the latest developments in visualization and visual analytics research and their applications. The authors describe the highlights of the 2016 event.
Gesehen am 21.08.2018